2014
DOI: 10.1007/s11242-014-0301-z
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic and Periodic Natural Convection for Moderate and High Prandtl Numbers in a Porous Layer subject to Vibrations

Abstract: A b s t r a c tThe analysis of natural convection for moderate and high Prandtl numbers in a fluid saturated porous layer heated from below and subject to vibrations is presented with a twofold objective. First, it aims at investigating the significance of including a time derivative term in Darcy's equation when wave phenomena are being considered. Second it is dedicated to reporting results related to the route to chaos for moderate and high Prandtl number convection. The results present conclusive evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…In the current study, it was shown experimentally that the rate of solidification is increased when vibrations were introduced during the solidification process. Since the effects of vibration would only affect the porous section and/or liquid we can assume that the results presented by Vadasz et al [8] in the porous medium might be linked to the results seen in the current study of solidification. It is also clear that vibrations do have an effect on the porous medium section as presented by Vadasz et al [8] for…”
Section: Effect Of Vibration On Solidification Timessupporting
confidence: 63%
See 4 more Smart Citations
“…In the current study, it was shown experimentally that the rate of solidification is increased when vibrations were introduced during the solidification process. Since the effects of vibration would only affect the porous section and/or liquid we can assume that the results presented by Vadasz et al [8] in the porous medium might be linked to the results seen in the current study of solidification. It is also clear that vibrations do have an effect on the porous medium section as presented by Vadasz et al [8] for…”
Section: Effect Of Vibration On Solidification Timessupporting
confidence: 63%
“…The third part is to determine the effects the vibrations had on the solidification time. The fourth part is to compare the results presented in the current study with the numerical results presented by Vadasz et al [8].…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations